2019
DOI: 10.1093/jamia/ocy176
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effects of implementing clinical pathways supported by health information technologies

Abstract: Objective Health information technology (HIT) interventions include electronic patient records, prescribing, and ordering systems. Clinical pathways are multidisciplinary plans of care that enable the delivery of evidence-based healthcare. Our objective was to systematically review the effects of implementing HIT-supported clinical pathways. Materials and Methods A systematic review protocol was developed including Medline, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
1
24
0
1
Order By: Relevance
“…Prior work has suggested that several factors may contribute to success of clinical pathways. 22,23 Some of these potential factors are related to health information technology (HIT), including using HIT to support quality, execution, and adherence to protocols. Our results support our hypothesis that use of the EHR to implement evidence-based ERAS guidelines can decrease costs without a resultant increase in 30-day readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has suggested that several factors may contribute to success of clinical pathways. 22,23 Some of these potential factors are related to health information technology (HIT), including using HIT to support quality, execution, and adherence to protocols. Our results support our hypothesis that use of the EHR to implement evidence-based ERAS guidelines can decrease costs without a resultant increase in 30-day readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…However, we implemented a rigorous methodology to control for both temporal trends and important confounder, a significant improvement over other studies that have attempted to evaluate pathways. 23 Furthermore, we used a similar surgical control group as a historical control. Third, given the low base rate of surgical complications in this population, we were not powered to detect differences in this important clinical outcome in the 18-month postimplementation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Given the informatics focus of the reviews, interventions were typically classified by a set of characteristics suitable for the types of technologies studied. Examples include clinical pathways (eg, clinical decision support, clinical documentation, dashboards) 9 and visualizations (eg, type of intervention [dashboard, mobile app, etc. ], type of visualization [planar, volumetric, network, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important that multiple databases are searched and that the databases are a match for the review topic. For example, Neame et al 9…”
Section: Formal Search Strategymentioning
confidence: 99%
See 1 more Smart Citation